Enhancing Enzymatic Hydrolysis of Cellulose by Ultrasonic Pretreatment - Roya Mahinpour; Mohammad Nabi Sarboluki (Iranian Journal of Chemistry & Chemical Engineering, 1998)
Slurries of rice-straw cellulose (obtained by delignification and removal of hemicelluloses from the powdered raw material) were subjected to ultrasonic waves at different intensities for various times (constant temperature). Susceptibility of the samples to cellulose-hydrolysis increased initially with pretreatment time, reaching a maximum or a constant level thereafter. Maximum glucose yield (~21%) was obtained under the following conditions: enzyme/substrate ratio 0.1; amplitude 18mm (peak to peak), and exposure time 30 minutes. This yield is 30X that of the starting raw material, 10X that of the untreated rice-straw cellulose and 12-13X that of the value reported by others regarding pretreatment of wheat-straw cellulose by phenol. Changing the enzyme/substrate ratio to 0.4 raises glucose yield to 42% under the same conditions. Removal of temperature control during pretreatment (50-80 °C) increases the yield up to ~30% without increasing the enzyme/substrate ratio.